Performance evaluation of aminated multi-walled carbon nanotubes incorporated with green synthesized iron nanoparticles for toxic dyes sequestration from textile wastewater - Titus Chinedu Egbosiuba; Cynthia Chukwuemeka; Jonah Chukwudi Umeuzuegbu; Nwanneka Chibuzo Mmonwuba; Ugochukwu Ewuzie; Monday Uchenna Okoronkwo; Valentine Chikaodili Anadebe; Saheed Mustapha; Ambali Saka Abdulkareem; Jimoh Oladejo Tijani; Ashish Patel; Virendra Kumar Yadav (Water Resources and Industry)
This study evaluates the performance of aminated multi-walled carbon nanotubes (AM-MWCNTs) integrated with zerovalent iron nanoparticles (ZVI) synthesized using cashew leaf (Anacardium occidentale) extract (AM-MWCNTs@ZVI) for the removal of Congo Red (CR) and Methylene Blue (MB) dyes from textile industrial wastewater. The nanocomposite was characterized using FTIR, XRD, BET, HRSEM, and HRTEM analyses, confirming its functional groups, crystalline structure, and enhanced surface area of 1050.4 m2/g. The ecological risk degree of the textile pollutants was assessed to determine the percentage concentrations of crystal violet, Congo red, methyl orange, methylene blue and rhodamine B. Batch adsorption experiments identified optimal parameters as pH 4 for CR and pH 8 for MB, contact time of 60 min, adsorbent dosage of 40 mg/L, and temperature of 40 °C. The Temkin isotherm model best described the adsorption process. Particularly, the maximum adsorption capacities of 450 mg/g and 422 mg/g were evaluated for CR and MB, respectively. Pseudo-second-order kinetics indicated chemisorption as the dominant mechanism. The nanocomposite demonstrated reusability with 88 % and 85 % removal efficiency for CR and MB, respectively, after six cycles. These results highlight AM-MWCNTs@ZVI as an effective, recyclable adsorbent for industrial wastewater treatment.